COMPUTER AIDED DESIGN ABSTRACT - Rojas Lazo, Oswaldo (2006)
Design is an activity that is projected to the problem solutions. These problems are analyzed by the human being when they try to adapt themselves to their surrounding environment, to satisfy their needs, using resources like CAD/CAE/CAM technologies. These technologies are currently applied through engineering concurrent methods. The most developed technique in the computer assisted engineering, is the application of the finite element analysis, which with the improvement of computer equipment, it has become in accessible techniques for all users. From design thru manufacturing, these techniques are used by the industries, having optimized costs, quality, time, safety, and so on.